Analysis of coupled thermal-hydro-mechanical processes during small scale in situ heater experiment in Callovo-Oxfordian clay rock introducing a failure-index permeability model. (June 2021) - Wang, Wenqing; Shao, Hua; Nagel, Thomas; Kolditz, Olaf
Abstract: To better understand the coupled thermo-hydro-mechanical processes in Callovo-Oxfordian (COx) claystone formations induced by heat emitting high-level radioactive waste, different scales of in-situ heater experiments have been conducted by ANDRA in the Meuse/Haute-Marne Underground Research Laboratory (M/HM URL) at Bure in France. In order to prove the predictability of numerical codes for a site-scale repository, two experiments, a small-scale (TED) and a full-scale experiment (ALC), have been intensively investigated by different teams within the international project DECOVALEX 2019. In this study, we present the numerical results obtained further developing and using the finite element OpenGeoSys (OGS) simulator with two novel approaches. (1) A failure index-dependent permeability model is introduced into the THM formulation to consider the effect of the permeability changes in the excavation-damaged zone (EDZ) on the pore pressure development during the excavation and subsequent heating phases, respectively. (2) A more general equation of state formulation for water according to the International Association for the Properties of Water and Steam (IAWPS) taking account of water and vapour behaviour is implemented to simulate the pore pressure increase induced by high temperature during heating. The complete model comparison study is presented in the Task E synthesis paper [46].